2022
DOI: 10.1007/s43657-021-00032-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progresses in Electrochemical DNA Biosensors for MicroRNA Detection

Abstract: MicroRNAs (miRNAs), as the small, non-coding, evolutionary conserved, and post-transcriptional gene regulators of the genome, have been highly associated with various diseases such as cancers, viral infections, and cardiovascular diseases. Several techniques have been established to detect miRNAs, including northern blotting, real-time polymerase chain reaction (RT-PCR), and fluorescent microarray platform. However, it remains a significant challenge to develop sensitive, accurate, rapid, and cost-effective me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…Studies have shown that these AS events play wide-ranging roles in the process of carcinogenesis, participating in cell proliferation, apoptosis, epithelial–mesenchymal transition, hypoxia, angiogenesis, and immune escape ( Chen et al, 2018 ; Du et al, 2022 ). These previous studies have shown that in addition to classic cis-/trans-acting regulation, there are many other mechanisms of AS regulation ( Yae et al, 2012 ; Picard, 2022 ; Zhang et al, 2022 ). Here, we use GSVA to conduct a comprehensive pathway analysis of 32,284 gene sets in MSigDB.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Studies have shown that these AS events play wide-ranging roles in the process of carcinogenesis, participating in cell proliferation, apoptosis, epithelial–mesenchymal transition, hypoxia, angiogenesis, and immune escape ( Chen et al, 2018 ; Du et al, 2022 ). These previous studies have shown that in addition to classic cis-/trans-acting regulation, there are many other mechanisms of AS regulation ( Yae et al, 2012 ; Picard, 2022 ; Zhang et al, 2022 ). Here, we use GSVA to conduct a comprehensive pathway analysis of 32,284 gene sets in MSigDB.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Despite growing interest in surface functionalization methods, several studies have focused on factors other than only electrode-miRNA conjugation and conductivity. 54…”
Section: Nanomaterials and Mirna Electrochemical Sensorsmentioning
confidence: 99%
“…Despite growing interest in surface functionalization methods, several studies have focused on factors other than only electrode-miRNA conjugation and conductivity. 54 In a study by Yang et al, a dual signal amplification biosensor was developed based on a nanowire array using multiwalled carbon nanotubes with the polypyrrole (PPy) (PPY/ MWCNTs) and GCE. The attachment of DNA and miRNA altered the conductivity and oxidation peaks due to the presence of CNTs and Prussian blue, respectively.…”
Section: Carbon-based Nanomaterials In Mirna Biosensormentioning
confidence: 99%
See 1 more Smart Citation
“…192 As a result, miRNA expression has been extensively studied as a potential biomarker for the diagnosis and prognosis of a wide range of illnesses, including cancer. [193][194][195] Mesoporous Au-Ag alloy films have a lot of potential for fabricating portable, high-performance miRNA sensors. 117 These DPV sensors enable ultrasensitive detection of miRNA with an LOD of 100 aM and possess activity in the dynamic range of 100 pM to 100 aM with good reproducibility (RSD, of o5%, for S/N = 3) (Fig.…”
Section: Biosensorsmentioning
confidence: 99%